2019
DOI: 10.1556/2006.8.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction in students: A qualitative examination of the components model of addiction using face-to-face interviews

Abstract: Background and aims: Smartphone use has increased markedly over the past decade and recent research has demonstrated that a small minority of users experience problematic consequences, which in extreme cases have been contextualized as an addiction. To date, most research have been quantitative and survey-based. This study qualitatively examined the components model of addiction for both "addicted" and "non-addicted" users. Methods: A screening tool comprising 10 dichotomous items was administered to 40 colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…The smartphone is sometimes seen as an extension of your own self. In addition to that, they assert that SRSA exerted an impact on their relationships with family members and friends ( Jameel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smartphone is sometimes seen as an extension of your own self. In addition to that, they assert that SRSA exerted an impact on their relationships with family members and friends ( Jameel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was necessary to implement ERT and, consequently, they started to enjoy more freedom to use their smartphones during classes; however, not always for academic purposes. Thus, the adolescents tend to get distracted and lose the focus on their studies, with negative repercussions in their academic performance ( Alosaimi et al, 2016 ; Jameel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of inhibition control ability is related to a variety of addictions and problem behaviors (D'Hondt, . Out-of-control smartphone use is also one of the main characteristics of individuals with SPA (Jameel, Shahnawaz, & Griffiths, 2019). Enhancing inhibition control skills in students with SPA is an effective method to reduce pathological smartphone use.…”
Section: Cognitive Training Inhibition Control Trainingmentioning
confidence: 99%
“…Various applications (APPs) together with the development of mobile internet make smartphone a powerful tool that is available almost anytime and anywhere. Because smartphones are Internet-enabled mobile phones, and have multiple functions, a series of tasks and activities such as work, study, entertainment, shopping and social communication can be conducted through this little intelligent devices (Jameel et al 2019). Therefore, some individuals spend more and more time on smartphones, and gradually, they develop smartphones dependence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the symptoms mentioned above, many studies have shown that there are significant positive correlations between mobile phone dependence risk and college students' perceived stress and loneliness (Samaha and Hawi 2016;Tan et al 2013). Although the adverse outcomes of smartphone dependence on physical and mental health have caught the attention of many researchers and participants, participants failed to quit this addictive behavior (Jameel et al 2019;Yang et al 2019). As a sample item included in the smartphone addiction scale (SAS) reads: Having tried time and again to shorten my smartphone use time, but failing all the time.…”
Section: Introductionmentioning
confidence: 99%